2015
DOI: 10.1016/j.juro.2015.03.092
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Duration of Penile Traction Therapy in Patients Undergoing Intralesional Injection Therapy for Peyronie's Disease

Abstract: Routine penile traction therapy during intralesional injection with interferon α-2b for Peyronie's disease may result in a small but subjectively meaningful improvement in stretched penile length, without affecting curvature, if used for at least 3 hours a day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 16 publications
0
45
1
2
Order By: Relevance
“…In a cohort of men with PD receiving therapy with intralesional interferon and PTT, only 31% were able to use the PTT device for 2 hours/day, of whom 56% were able to use it for 3 hours/day (overall compliance of 17% for 3 hours/day). 11 In contrast, in the present study, 92% of men in the CCH þ RestoreX group and 87% in the CCH þ other PTT group were able to use the device for 30 minutes/day. Thus, the ability to achieve significant improvements with a shorter duration of PTT use is critical to the clinical utility of this therapy.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In a cohort of men with PD receiving therapy with intralesional interferon and PTT, only 31% were able to use the PTT device for 2 hours/day, of whom 56% were able to use it for 3 hours/day (overall compliance of 17% for 3 hours/day). 11 In contrast, in the present study, 92% of men in the CCH þ RestoreX group and 87% in the CCH þ other PTT group were able to use the device for 30 minutes/day. Thus, the ability to achieve significant improvements with a shorter duration of PTT use is critical to the clinical utility of this therapy.…”
Section: Discussioncontrasting
confidence: 85%
“…Given previous publications demonstrating improvements with other PTT devices only at durations of 3 hours/day, we performed a subset analysis of men who reported a mean duration of use of 3 hours/day with other PTT devices during the CCH injection period. 6e9, 11 Overall, 16% (7 of 45) of the men in whom use for 3 hours/day was recommended were able to achieve this duration, with no significant differences noted compared with CCH alone in absolute curvature (-22.9 vs -20.3 ; P ¼ .70), percent curvature (40.8% vs 31.2%; P ¼ .64), absolute length (þ0.67 cm vs -0.7 cm; P ¼ .14), and percent length (5.8% vs -3.5%; P ¼ .21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hellstrom's group has recently reported that routine penile traction therapy during intralesional injection with interferon α-2b for Peyronie's disease may result in a small but subjectively meaningful improvement in stretched penile length, without affecting curvature, if used for at least 3 hours a day. 61 It must be noted that all studies vary in time the devices are applied, and the manner in which this is performed. For many patients, there is no defined teaching and follow-up protocol, and use is self-reported; as with any physiotherapy, a "perfect" stretch may be more useful than a prolonged traction session with the device improperly used or incomplete traction.…”
Section: Mechanical Therapy -Penile Tractionmentioning
confidence: 99%
“…However, while modeling possibly improves curvature, it may have a negative effect on penile length when not performing simultaneous PTT [51]. Nonetheless, Yafi et al [52] studied patients undergoing intralesional IFN α2β treatment and showed that those who received PTT daily had a very modest (3 mm), yet significant increase in stretched penile length. While PTT does not appear to be effective in isolation to treat PD, it may have a role in combination treatment, particularly with the goal of maintaining or improving penile length.…”
Section: Other Nonsurgical Treatmentsmentioning
confidence: 99%